Pulmonary Capillary Hemangiomatosis: A Rare Cause of Pulmonary Arterial Hypertension, Presenting as Supraventricular Tachycardia - Ganganpalli Dattaprasad; Umesh Kumar Chandra; Sumit Kumar Vishwakarma; V.P. Pandey; Sanjay Dubey (International Journal of Cardiovascular Practice, 2019)
With a prevalence of less than 1/million, Pulmonary Capillary Hemangiomatosis is a rare disorder of capillary proliferation in the alveolar septae leading to pulmonary arterial hypertension and mimics pulmonary veno-occlusive disease.